Advances in basic and translational tuberculosis research: Proceedings of the first meeting of RePORT international. (January 2017) - Geadas, Carolina; Stoszek, Sonia K.; Sherman, David; Andrade, Bruno B.; Srinivasan, Sudha; Hamilton, Carol D.; Ellner, Jerrold
Abstract: RePORT International is a collaborative research network of investigators from multiple countries and institutions with the goal of establishing a bio-repository of specimens and clinical data for the study of active TB and latent TB infection (LTBI). During the first meeting of RePORT International in Boston, Massachusetts, the results of research pertinent to TB control and eradication were presented, including advances in the research of Mycobacterium tuberculosis (MTB) persistence and drug resistance, TB diagnostics, drug and vaccine development.